Theory of Metalanguage and Description of Autonymy in Slovenian - Trojar, Mitja (Jezikoslovni zapiski, 2023)
This article describes the relation between metalanguage and object language, as well as essential concepts used in the description of metalanguage and linguistic terminology. The article outlines special features of Slovenian metalanguage, with special attention devoted to autonymy in linguistics texts.